Bioelectrocatalysis: Graphene Carrier for Magneto‐Controllable Bioelectrocatalysis (Small 4/2014). Issue 4 (February 2014) - Wan, Pengbo; Yin, Shengyan; Liu, Lili; Li, Yuangang; Liu, Yuanjun; Wang, Xiaotian; Leow, Wanru; Ma, Bing; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> Fuel‐free magneto‐controllable bioelectrocatalysis based on a graphene carrier loaded with redox‐active cargo as an electron mediator is reported by B. Ma, X. D. Chen, and co‐workers on page 647. The activation and deactivation of the redox‐active cargo's redox activity by the magnetically driven complex graphene carrier can be employed for magneto‐switchable bioelectrocatalyzed oxidation of glucose by glucose oxidase between active and inactive electrocatalytic states. This development has great potential in magneto‐switchable biofuel cells, fuelfree magnetobioelectronics, controlled biomedical drug delivery, etc. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>